Supporting international cooperation on biogas : the DiBiCoo project - Ma, Chuan (2022)
The DIBICoo project supports the European biogas/biomethane industry and the biogas development in developing and emerging countries by preparing markets for the export of sustainable biogas/biomethane tecnologies from Europe to developing and emerging countries. This is achieved by the development and application of innovative digital and no digital support and matchmaking tools and actions, by knolwledge transfer and capacity building as well aas by the preparation of demo cases up to prefeasibility stage. This will increase the share of renewable energiews, both in Europe and in import countries. This paper addresses biogas-relevant framework conditions in the importing and exporting countries, the status of research and development needs of biogas technologies in the importing countries as well as opportunities for European countries.